Computer simulation of reflectance due to dielectric mirror - Darkwi, A. Y.; Ibrahim, K. (Libyan Journal of Science &Technology, 2022)
The present work is calculating the reflectance due to stacked multilayer dielectric material. The calculation is based on the analysis of the characteristic matrix of an arrangement of n layers, each containing parameters that dealing with reflection (reflective index, optical thickness, wavelength of incident wave, angle of incident wave). The implication of this calculation on a dielectric mirror is pointed out. For certain arrangement of dielectric layers with a particular thickness, maximum reflectance can be obtained. In this work, FORTRAN program has been written to obtain the product of matrices. Calculation of reflectance and transmittance which are particularly needed in this context have been obtained.